Evaluation of genetic diversity and DNA fingerprinting of 19 standard reference rice varieties using SSR markers - Long, Tran; Minh Cuc, Luu; Quang Sang, Nguyen; Xuan Hoi, Pham (Vietnam Journal of Biotechnology, 2020)
Molecular markers are advanced-tools for identifying new varieties at DNA levels. According to the International Union for the Protection of New Varieties ofPlants, new breeded varieties need to be tested for the Distinctness, Uniformity and Stability (DUS), before being recognized as the new ones. Traditional DUS criteria based on 62 - 65 morphological and biochemical characteristics, which evaluated on comparison of new varieties with 19 standard reference varieties for traits of interest. Study on the genotypic polymorphism of 19 standard reference rice varieties provides genotypic information of these varieties for the evaluation of new rice varieties based on genotyping analysis. The reference marker set (30 markers) was used to evaluate the genetic diversity and DNA fingerprinting of 19 standard reference rice varieties. The results showed the similarity coefficient of 19 varieties varied from 0.04 to 0.548. At the genetic similarity coefficient of 0.1, the 19 rice varieties divided into two main groups. Group one included 3 varieties: DH1, DH5, DH13. Group 2 included the remaining 16 varieties. Inside group two, phylogenetic tree divided into two main branches at the genetic similarity coefficient of 0.3. Branch 1 includes 5 varieties including DH2, DH6, DH10, DH11 and DH7. The 11 remaining varieties were in the branch 2. The most closely varieties were DH6 and DH10 with the genetic similarity coefficient of 0.548. This study shows that, the standard reference varieties have high uniformity and high genotypic polymorphism, could used for testing new varieties based on genotyping by DNA fingerprinting combining with phenotype.